Knowledge Regarding Drug Abuse Among Adolescents in School - Chettri, Poonam Khadka; Budhathoki, Bamita; Shrestha, Rhinu; Giri, Sabitri; Shrestha, Sunita; Limbu, Sajana (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Drug abuse is a common public health problem worldwide and a global threat. The objective of the study was to assess the knowledge regarding drug abuse among adolescents in a School of Dharan. Method: A descriptive cross-sectional design was carried out among 144 students of Sagarmatha SD College. Probability proportionate sampling method was used and data was collected through self-administered Questionnaire and analyzed by descriptive and inferential statistics using SPSS version 25 and findings were presented in tabulated form. Findings: More than half (54.9%) of the respondents had adequate level of knowledge. Adequate knowledge was present on meaning of heroin was (54.9%).Adequate level of knowledge present influencing factors ((70.1%) of the drug abuse is peer pressure, route of administration of marijuana and heroin (81.4%) and (59%) respectively. However, inadequate knowledge was present regarding meaning of drug abuse (34.02%) and heroin (13.2%) respectively, withdrawal symptoms of marijuana and heroin (20.1%), 24.3% & regarding preventive aspects of drug abuse & treatment were 24.3% and 11.1%. There was no significant association found between level of knowledge with demographic variables. Conclusion: More than half of the respondents had adequate level of knowledge regarding drug abuse despite of this, there is inadequate level of knowledge regarding meaning of drug abuse, their effects and preventive & treatment measures. Which indicates need awareness program on drugs abuse to adolescents.